2020
DOI: 10.1089/acm.2019.0231
|View full text |Cite
|
Sign up to set email alerts
|

Dry Cupping, Ischemic Compression, or Their Combination for the Treatment of Trigger Points: A Pilot Randomized Trial

Abstract: Background: Chronic neck pain (NP) attributed to myofascial pain syndrome is one of the particularly common skeletal muscle disorder associated with the hyperirritable zone in the taut band of muscle. Trigger points (TPs) are the physical interpretation of the myofascial pain syndrome. In the United States, 30%-85% of pain patients have been affected by myofascial TPs.Objectives: To reveal preliminary evidence on the clinical efficacy of ischemic compression therapy, dry cupping, and their combination on impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 31 publications
3
22
0
1
Order By: Relevance
“…e results of this study can be understood with the reports of previous studies declared by Kashyap et al [23], Iqbal et al [21,22], Hong et al [39], Martín-Pintado-Zugasti et al [9], Benito-de-Pedro et al [12], Nasb et al [41], Hanten et al [19], Chaitow [13], Fryer and Hodgson [3], Fernándezde-las-Peñas et al [36], Cagnie et al [16,20], Capo-Juan et al [17], and other researchers. e results achieved by these authors are similar to the results achieved in this study for the combination of two manual techniques (MET plus ICT) in the management of neck pain and muscle tenderness due to upper trapezius active MTrPs.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…e results of this study can be understood with the reports of previous studies declared by Kashyap et al [23], Iqbal et al [21,22], Hong et al [39], Martín-Pintado-Zugasti et al [9], Benito-de-Pedro et al [12], Nasb et al [41], Hanten et al [19], Chaitow [13], Fryer and Hodgson [3], Fernándezde-las-Peñas et al [36], Cagnie et al [16,20], Capo-Juan et al [17], and other researchers. e results achieved by these authors are similar to the results achieved in this study for the combination of two manual techniques (MET plus ICT) in the management of neck pain and muscle tenderness due to upper trapezius active MTrPs.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, combination therapy including ICT has proven to be more effective than the ICT alone, which supports the result of our study. Nasb et al (2019) reported that the combination of ICT with dry cupping for 4 weeks has shown more effectiveness than either ICT or dry cupping alone in the improvement of PPT, NDI, and ROM scores significantly [41]. Hanten et al (2000) examined the efficacy of a home program containing ischemic compression followed by sustained stretching over active MTrPs.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have confirmed that dry cupping can improve the symptoms of myofascial pain syndrome and restore activity [ 5 , 21 ], and our findings were consistent with those of these studies. However, the studies mostly used subjective clinical symptoms to evaluate the effect of cupping on improving myofascial pain, and our study was characterized by a combination of subjective questionnaires and quantitative assessments of objective soft tissue compliance.…”
Section: Discussionsupporting
confidence: 93%
“…The study was powered to detect an effect size of the primary outcome measure of 0.6, which was estimated based on the findings of a pilot study on dry cupping in myofascial pain syndrome [ 16 ]. To detect this effect with 80% power and a two-sided α of 0.05, a sample of eight patients was needed for each group.…”
Section: Methodsmentioning
confidence: 99%
“…İskemik grupla kupa grubu arasında NDI, PPT ve NROM açısından anlamlı farklılık tespit edilmemiştir. 84 Çin'de yapılan, kupa ve akupunktur kombinasyon tedavisinin lomber miyofasiyal ağrı sendromundaki etkinliğini inceleyen bir çalışmada, bu tedavinin VAS skorunu istatistiksel olarak anlamlı şekilde azalttığı rapor edilmiştir. 85…”
Section: Mi̇yofasi̇yal Ağri Sendromuunclassified